Exploring the Non-Tax Revenues of Environmental Management Bureau XI - Annie R. Degala (PT FORMOSA CENDEKIA GLOBAL, 2023)
The first is tax revenue, whereas the second is non-tax revenue. We are all aware of the importance of the economy to the survival of a nation. The nation's priority is the economy. The nation's progress is dependent on economic expansion. However, many individuals disregard how non-tax revenue affects the economy, preventing the nation from fully utilizing non-tax revenue to spur economic growth. Hence, it's indeed crucial to examine the non-tax revenue management system in light of how non-tax revenue affects the economy. This paper focuses on exploring the non-tax revenue of EMB XI and provide recommendations for enhancing the non-tax revenue management system. This study intends to investigate the key determinants of non-tax revenue collections for Region XI of the Environmental Management Bureau from 2017 to 2021. Additionally, the collections were calculated both before and after accounting for inflation adjustment. Based on secondary data extracted from EMB XI for the years 2017 to 2021, it was created. To investigate the significance of accounting for inflation adjustments in the collected non-tax revenues, descriptive and exploratory study designs are used.